ANALYSIS OF ELECTION ADMINISTRATIVE VIOLATIONS (CASE STUDY: RE-VOTING IN THE 2024 GENERAL ELECTION IN TEGAL CITY) - Fathurohman, Septio; Zainudin, Arif; Widodo, Agus Setio (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
Administrative violations are problems that often occur in every election from the 2019 General Election to the 2024 General Election, one of which occurred in Tegal City. This paper aims to analyze administrative violations that occurred at TPS 28 Debong Tengah Village, Tegal Selatan Subdistrict, Tegal City. This research uses literature review analysis with archives of the Tegal City Bawaslu report and previous researchers' studies in the form of scientific articles as data. The results showed that the occurrence of administrative violations at polling station 28 Debong Tengah Village, South Tegal Subdistrict, Tegal City was due to the opening of the ballot box which was not in accordance with the regulations by KPPS as the election organizer at the lowest level, causing re-voting. In addition, KPPS was considered to lack integrity because it still needed to be reminded by supervisors regarding the procedures for implementing voting.